Multi-objectives probabilistic Aggregate production planning with practical application - جواد لميعه باقر; جيتر علاء شنيشل (Journal of Economics and Administrative Sciences, 2015)
In this research, has been to building a multi objective Stochastic Aggregate Production Planning model for General al Mansour company Data with Stochastic demand under changing of market and uncertainty environment in aim to draw strong production plans. The analysis to derive insights on management issues regular and extra labour costs and the costs of maintaining inventories and good policy choice under the influence medium and optimistic adoption of the model of random has adoption form and had adopted two objective functions total cost function (the core) and income and function for a random template priority compared with fixed forms with objective function and the results showed that the model of two phases with k = 4 is the best model of random which contributed to reducing costs by approximately 7%. It was also a statement that the change in the total costs will be changed by the possibilities associated with cases predicted demand (scenarios) where we note the low cost and with a high probability of low demand. In contrast, the total cost increases with increasing demand. Because the change in the possibilities leads to change in the Production plan for future. As well as the building and solving model multi-objectives by constraint method improved (augmented) and the results were derived a set of acceptable solutions rather than a single solution and thus can be a decision-maker to choose the best solution for the specific case of the optimization problem of multiple objectives, was Form solution using the developed software GAMS